2015
DOI: 10.1073/pnas.1422363112
|View full text |Cite
|
Sign up to set email alerts
|

Conserved SMP domains of the ERMES complex bind phospholipids and mediate tether assembly

Abstract: Membrane contact sites (MCS) between organelles are proposed as nexuses for the exchange of lipids, small molecules, and other signals crucial to cellular function and homeostasis. Various protein complexes, such as the endoplasmic reticulum-mitochondrial encounter structure (ERMES), function as dynamic molecular tethers between organelles. Here, we report the reconstitution and characterization of subcomplexes formed by the cytoplasm-exposed synaptotagmin-like mitochondrial lipid-binding protein (SMP) domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
207
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(232 citation statements)
references
References 50 publications
16
207
0
4
Order By: Relevance
“…The SMP domains of Mdm12 and Mmm1 both exhibit PL binding activity with preference for PC (89). In addition, a ternary complex was described in which cytosolic Mdm12 bridges the integral ER Mmm1 to the mitochondrial Mdm34 (89). The structural and biochemical characterization of the three SMP domain-containing components of the ERMES complex provides evidence of the involvement of these proteins in the mechanical tethering of both compartments and supports their plausible role in mediating lipid transfer.…”
Section: Ermes: a Tethering Complex With Lipid Transfer Activitymentioning
confidence: 81%
See 2 more Smart Citations
“…The SMP domains of Mdm12 and Mmm1 both exhibit PL binding activity with preference for PC (89). In addition, a ternary complex was described in which cytosolic Mdm12 bridges the integral ER Mmm1 to the mitochondrial Mdm34 (89). The structural and biochemical characterization of the three SMP domain-containing components of the ERMES complex provides evidence of the involvement of these proteins in the mechanical tethering of both compartments and supports their plausible role in mediating lipid transfer.…”
Section: Ermes: a Tethering Complex With Lipid Transfer Activitymentioning
confidence: 81%
“…Structural analyses of the SMP domains of Mdm12 and Mmm1 revealed that they assemble into a heterotetramer forming an elongated crescent shape in which Mmm1 forms a central homodimer and a monomer of Mdm12 binds to each end of this dimer. A hydrophobic channel traverses this elongated heterotetramer (89). The SMP domains of Mdm12 and Mmm1 both exhibit PL binding activity with preference for PC (89).…”
Section: Ermes: a Tethering Complex With Lipid Transfer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…S1) (15)(16)(17)(18)(19). The SMP domain exhibits a β-barrel structure, which is common to the tubular lipid binding superfamily (20), and harbors lipids in its hydrophobic cavity (21)(22)(23). C2 domains are autonomously folded structures that bind to lipids and Ca 2+ (12,24,25).…”
Section: +mentioning
confidence: 99%
“…The ER-mitochondria encounter structure (ERMES), also involved in ER-mitochondria tethering, is a multifunctional protein complex implicated in both lipid transfer and mitochondrial outer membrane protein assembly ( AhYoung et al , 2015; Kornmann et al , 2009; Meisinger et al , 2006, Meisinger et al , 2007; Wideman et al , 2013; Wideman et al , 2010). However, ERMES as an ER-mitochondria tether is limited to a subset of eukaryote taxa ( Wideman et al , 2013), suggesting that a universal ER-mitochondria tethering complex might exist.…”
Section: Introductionmentioning
confidence: 99%